Dialogue with the Bible in the Poetical Dramas by Lesya Ukrainka: Philosophical Reflections and Dominant Symbols - Hirnyak, Maryana (Respectus Philologicus, 2022)
The article posits that the Biblical code is one of the most important pillars in the interpreting the literary works by Lesya Ukrainka, one of Ukraine’s renowned writers. Her verse dramas foreground Biblical intertextuality, which becomes a starting point for intellectual debates in the Ukrainian ‘fin de siècle’ on such essential problems as freedom and love, social and mental slavery, and the mission of art. The problems of (mis)treating the essence of God’s Kingdom and the human relationship with God are also centrepieces of Lesya Ukrainka’s dialogicality with the Bible. In the writer’s verse dramas, the explicit and implicit Biblical intertexts specify the active double-voiced discourse, which exhibits an interaction of the different consciousnesses. Following this, the text of the Scriptures provides the background for the dominant symbols (harp, stone and light) that can be actualized by the informed reader both through the allusions and via the reminiscences in Lesya Ukrainka’s dramatum.